A simple phenazine derivative fluorescence sensor for detecting formaldehyde. (19th October 2022) - Wei, Tai-Bao; Dang, Li-Rong; Hu, Jian-Peng; Jia, Yu; Lin, Qi; Yao, Hong; Shi, Bingbing; Zhang, You-Ming; Qu, Wen-Juan
Abstract : We developed fluorescence sensor for detecting HCHO. Such molecular sensors have great potential to be utilized. We hope that this simple fluorescent probe can arouse widespread attention in the fields of molecular sensing and food chemistry. Abstract : Formaldehyde (HCHO) is a common chemical raw material that is toxic and harmful in nature. Excessive HCHO content has extremely significant effects on the atmospheric environment and human health. To this end, herein, we report a 1 H -[1, 2, 3]triazole[4, 5- b ]phenazine (PHTA ) probe that is capable of sensing HCHO via a rapid change in its fluorescence color or intensity in the presence of the gas and solution. PHTA was directly loaded on a silica gel plate to make a portable solid sensor HCHO kit, which achieves the sensitive and selective detection of gaseous and liquid HCHO. Whether as a solid or liquid sensor for HCHO, PHTA allows for safer and more convenient use compared to other sensors. 1 H -[1, 2, 3]triazole[4, 5- b ]phenazine, Fluorescent sensor, VOCs, Formaldehyde detection.